Penggunaan Alkohol dalam Upaya Pencegahan Covid-19; Analisis Maslahah Mursalah - Mallarangang, Andi; Haddade, Abdul Wahid (Universitas Islam Negeri Alauddin Makassar, 2022)
This article aims to describe and analyze the maslahah mursalah method of using alcohol as an effort to prevent covid-19. In answering these problems, the author uses library research which is guided by the management of data obtained from various literatures. The sources of data found include primary and secondary data. This research approach uses a qualitative and normative-juridical approach which is something based on literature study by examining scientific works that are directly related to the object being studied and related legal provisions, then analyzing in the literature that has relevance to the problem being discussed, then review and conclude. The results of this study indicate that, there are many benefits contained by alcohol in preventing the transmission of covid-19 through the analysis of maslahah mursalah. In this paper there are many explanations about the dangerous impact of covid-19 which is a terrible scourge for all mankind, because this disease attacks the human respiratory system to cause death that spreads through touch (droplets). However, mankind is always making new breaktroughs in preventing this, namely using alcohol as a very effective cleaning tool in the covid-19 outbreak situation (Handsanitizer and Disenfektan) because the content in alcohol is useful as a bacteria killer because alcohol itself is hot and flammable. Through the analysis of maslahah mursalah, there are various kinds of Islamic legal provisions in using alcohol, because maslahah mursalah itself is a method to achieve goodness and benefit. The explanation about alcohol itself has been listed in the texts, which is something that is prohibited but is an emergency need ini midst of covid-19 outbreak. Alcohol which is something that is prohibited will be useful as a cleaning tool to prevent the transmission of covid-19